Urejanje pravic v kolektivnih pogodbah in vloga sindikatov po novem zakonu o delovnih razmerjih - Kresal Šoltes, Katarina (Delavci in delodajalci, 2013)
The new labour legislation has been adopted as one of the key structural reforms to boast the economic development and to end the crisis. But these structural reforms should not undermine mechanisms of collective bargaining and the role of trade unions to promote and defend workers' respective interests, as this right is recognised by the applicable law and is the cornerstone of the European social model as well. The contribution deals with the legal issues regarding the effects diverse new Employment relationship act has on the recent system of collective agreements and the role of trade unions in employer's practices.
Keywords: delovna razmerja; delovne pogodbe; delovno pravo; Evropska unija; reforma; sodna praksa; spremembe